Persepsi Kontrol Perilaku dan Niat terhadap Perilaku Memilah Sampah di Perusahaan Jasa Konstruksi Migas - Ambar Lestari; Wustari L Mangundjay; Dwi Nowo Martono (Universitas Andalas, 2022)
Abstract. The growing economic sector and people’s living standards growth have caused the number of domestic solid waste in urban areas to increase. The paper aims to analyze correlation between perceived behavioral control and intention to sort waste towards waste sorting behavior at work by applying Theory of Planned Behavior (TPB) from Icek Ajzen. This study uses a quantitative approach towards 251 respondents using likert scale (1 – 4) as the instrument. The measuring instrument are Pearson Product Moment and Multiple Correlation. The results of this study indicate that (1) there is a correlation between perceived behavioral control and waste sorting behavior (0.371); (2) there is a correlation between intention to sort waste and waste sorting behavior (0.313); (3) there is a strong correlation between perceived behavioral control and intention to sort waste (0.802); (4) correlation between perceived behavioral control and intention towards waste sorting behavior shows R2 = 0.372. Company’s intervention through the provision of appropriate types of trash bins with close proximity to the employee's position at work is needed to improve waste sorting behavior. Keywords: intention, perceived behavioral control, TPB, waste sorting